The Drosophila muscle LIM protein, Mlp84B, cooperates with D-titin to maintain muscle structural integrity. - Clark, K.A.; Bland, J.M.; Beckerle, M.C. (Journal of Cell Science, 2007)
Muscle LIM protein (MLP) is a cytoskeletal LIM-only protein expressed in striated muscle. Mutations in human MLP are associated with cardiomyopathy; however, the molecular mechanism by which MLP functions is not established. A Drosophila MLP homolog, mlp84B, displays many of the same features as the vertebrate protein, illustrating the utility of the fly for the study of MLP function. Animals lacking Mlp84B develop into larvae with a morphologically intact musculature, but the mutants arrest during pupation with impaired muscle function. Mlp84B displays muscle-specific expression and is a component of the Z-disc and nucleus. Preventing nuclear retention of Mlp84B does not affect its function, indicating that Mlp84B site of action is likely to be at the Z-disc. Within the Z-disc, Mlp84B is colocalized with the N-terminus of D-titin, a protein crucial for sarcomere organization and stretch mechanics. The mlp84B mutants phenotypically resemble weak D-titin mutants. Furthermore, reducing D-titin activity in the mlp84B background leads to pronounced enhancement of the mlp84B muscle defects and loss of muscle structural integrity. The genetic interactions between mlp84B and D-titin reveal a role for Mlp84B in maintaining muscle structural integrity that was not obvious from analysis of the mlp84B mutants themselves, and suggest Mlp84B and D-titin cooperate to stabilize muscle sarcomeres.